Characterizing the biophysical conditions for improved planning and designing of locally-led sustainable land management practices: the case in Halaba, Ethiopia - Girma, R.; Mekuria, Wolde; Moges, A.; Smith, J.; Hallett, P. (International Water Management Institute, 2025)
Spatially customized land management strategies are crucial for mitigating land degradation and fostering effective landscape restoration. A deep understanding of local biophysical conditions ensures that interventions are both contextually relevant and impactful, promoting long-term environmental sustainability and delivering socio-economic benefits to local communities. With this consideration, this report, drawing on data collected through field surveys, GIS, and remote sensing techniques, uses Halaba, Ethiopia, as a case study to highlight the region’s varied biophysical conditions and their implications for the design and planning of sustainable land management (SLM) practices. This document is intended for agricultural and natural resource management professionals involved in the design, planning, implementation, and monitoring of SLM practices.